Neonatal intrathoracic neuroblastoma: unusual presentation with haemothorax - Joana Jardim; Gustavo Rocha; Susana Pissarra; Maria Bom Sucesso; Conceição Souto-Moura; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2015)
Thoracic neuroblastomas are rare in the neonatal period. They may be asymptomatic or cause respiratory distress. Congenital haemothorax present at birth, as the result of intravascular disseminated coagulopathy, is an uncommon initial presentation of intrathoracic neuroblastomas.